Comparison of HBV DNA Quantitative Log in Patients Hepatitis B with Telbivudine Therapy Compared with Tenofovir Therapy in Saiful Anwar General Hospital Malang: January 2016 - December 2017 - Nasution, Muhammad Imanuddin; Mustika, Syifa (Universitas Brawijaya, 2021)
Background: Hepatitis B is a health problem with high endemic in Indonesia. Hepatitis B virus infection is transmitted parenterally, has a risk of liver cirrhosis and hepatocellular carcinoma. Detection and quantification of HBV DNA are markers of active HBV replication and determine treatment options for hepatitis B. Methods: compare log reduction of HBV DNA in patients treated with Telbivudine and Tenofovir. Results: There was no significant difference in HBV DNA levels between before and after Tenofovir treatment, namely 6 months follow-up (OR 95% CI = 5.41 [0.83 - 35.16], p = 0.0770) and 12 months (OR 95% CI = 5.39 [0.83 - 34.99], p = 0.0780). Telbivudine administration showed a significant difference in HBV DNA levels between before and after treatment at 6 months follow-up (OR 95% CI = 13.69 [4.53 - 41.40], p = 0.0001) and 12 months (OR 95% CI = 13.69 [ 4.53 - 41.41], p = 0.0001). Comparison of Tenofovir and Telbivudine therapy showed no significant difference at 6 months follow-up (OR 95% CI = 0.44 [0.10 - 1.88], p = 0.2690) but significant at 12 months follow-up (OR 95% CI = 6.23). [1.39 - 27.97], p = 0.0170). Conclusion: Â There was a significant difference between the administration of Telbivudine as a treatment for hepatitis B with lower serum HBV DNA levels compared with the administration of Tenofovir at 12-month follow-up therapy.